Peningkatan Kemampuan Menulis Cerita Fiksi Dengan Menggunakan Gambar Seri Pada Siswa Kelas V SD - Retina Retina (Jurnal Riset Teknologi dan Inovasi Pendidikan (Jartika), 2019)
This research aims to describe the Implementation of Discovery Method can improve Indonesian Language Learning Achievement The Subject of Writing Stories in Class V Students of SDN Loang Tuna. The subject of this study was the fifth grade students of Loang Tuna Elementary School, the study population was all fifth grade students of Loang Tuna Elementary School, amounting to 29 people. The data collection method used in this study is the method of observation and test of learning outcomes to determine the increase in learning achievement in Indonesian, the subject of writing stories by applying the discovery method. The results of this study that the average value of all students is from the average value of 62.06 in the first cycle to 80.34 in the second cycle, with the percentage of learning completeness of 93.10%, which was previously only 48.27%. It was concluded that the application of discovery methods can improve learning achievement in Indonesian, the subject of writing stories in class V SDN Loang Tuna. This is proven by the increase.